Fault ride-through of fully enclosed squirrel-cage induction generators for wind farms in Thailand - Daunghom K. (2017)
The increasing amount of wind power generation in Thailand power systems requires stability analysis considering interaction between wind-farms and transmission systems. Dynamics introduced by dispersed wind generators at the distribution level can usually be neglected. However, large wind farms have a considerable influence to power system dynamics and must definitely be considered for analyzing power system dynamics. For this purpose, a detailed dynamic model of fully enclosed squirrel cage induction generator with gearbox (full-scale power electronics converters) of a 2.3 MW wind turbine with has been implemented using the modeling environment of the simulation software DIgSILENT PowerFactory. For investigating grid compatibility aspects of this wind generator concept, a model of a 96.6 MW wind farm, with typical layout, based on 42 wind turbines of the 2.3 MW-class has been analyzed. This paper is focusing on transient stability and fault ride through capability when the grid voltage has dropped to a very low value. © 2010 IEEE.